Performance Evaluation of Soiling Mitigation Technique for Solar Panels. - Afolayan, M. A.; Olayiwola, T. N.; Nurudeen, Q. T.; Ibrahim, O.; Madugu, I. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Soiling is the accumulation of dust, leaves, and debris on the surface of photovoltaic modules which affects its overall conversion efficiency. Globally, several researches have indicated that with an increase in dust accumulation, the efficiency of the solar panels can drop by approximately 50%. This research aimed at increasing the efficiency of solar panels by mitigating the effects of soiling. The panel was incorporated with a dust sensor that senses increment in dust settlement and a DC Fan/blower which was placed in a position covering the surface of the panel. The speed of the installed fan can be varied using an L293D motor driver. It is actuated when the light intensity of the module falls below a set threshold. Solar energy parameters of the panel were measured and displayed on the constructed onboard controller. A comprehensive analysis was carried out on the design and the results show a 72%  increase in efficiency after mitigation which reflects that controlled wind is an ideal technique in eliminating dust on solar panels.